Towards Hybridity: Dance, tourism and cultural heritage. (18th May 2020) - Cisneros, Rosemary; Crawley, Marie-Louise; Whatley, Sarah
Abstract : This article considers the many layered and multi-faceted questions of hybridity as interdisciplinary encounter through the lens of a central case study – the EU-funded project, CultureMoves (2018-2020), on which the Centre for Dance Research (C-DaRE) was a collaborating partner. With Europeana principles as a backdrop for the re-use of cultural heritage content, CultureMoves was an 18-month long project that aimed to develop a series of digital tools enabling new forms of touristic engagement and dance educational resources. The CultureMoves project is marked by hybridity in terms of its very interdisciplinarity, in its rooting in an interpretation of 'creative tourism' (Richards and Raymond 2000 ; Richards and Marques 2012 ) as a means of enhancing encounters between artists, tourists and communities and in its focus on the expanded sense of the coming together of dance artist and cultural heritage site. With particular reference to the broader field of creative tourism, this article reflects on the key questions and assumptions that underlie existing and potential collaborations between the dance research/ education, digital technology and tourism sectors, and which prepared the terrain for the toolkit development. The article will also provide a close examination of experiments in the project that intend to awaken new experiences of space and place, and dormant histories, through bringing dancing bodies into relation with the built environment and digital technologies, as an intervention into creative (and cultural) tourism. Marked by the intersection of the human and non-human, and the differing expectations of stakeholders and audiences, the discussion also considers where experiments fail, to offer a view of what that tells us about the limits of hybridity in performance.